Increasing research capacity in adult social care: a research capacity-building partnership in Kent and its theory of change. [version 2; peer review: 2 approved] - Nick Smith; Sarah Hotham; Alison Charles; Georgina Walton; Ferhana Hashem; Ann-Marie Towers; Jolie R Keemink; Rasa Mikelyte; Wenjing Zhang (NIHR Open Research)
This paper describes the development of an adult social care (ASC) research capacity-building partnership and the corresponding theory of change that underpins this work. In 2021, the National Institute for Health and Care Research (NIHR) funded six social care capacity building partnerships across England to improve the quality and quantity of social care research. These partnerships facilitate collaborative working between universities, local authorities, practitioners, providers, and people with lived experience. The Kent Research Partnership was established as one of the partnerships. Taking a co-produced approach, the Kent Research Partnership is a four-year partnership that aims to improve care quality by investing in and valuing the social care workforce and developing a culture of research and evidence-based practice and innovation. The Kent Research Partnership includes four interlinked streams of work- Communities of Practice, Researcher in Residence, Fellowships, and Access to Research. In addition, a fifth, cross-cutting workstream is dedicated to involving those with lived experience of ASC. To ensure robust programme planning and evaluation, we developed Theory of Change models for the overall partnership and each workstream. Within these models, we also how the Kent Research Partnership intends to change behaviour using the Behaviour Change Wheel as the underpinning model.